The English Teaching Problems of High Schools at Taunggyi City in Myanmar - Ven. Pannasami; Kanokkamalade , Veerakarrn; Pintrymool, Narongchai (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The purpose of this study were to study the English teaching problems of High Schools at Taunggyi city in Myanmar, and to propose the solutions of these problems. The study was a quantitative research, it was conducted by the means of questionnaires and semi-structured interviews. The participants of the study were 100 students, 10 English teachers from five High Schools for questionnaires, and five Headmasters from five High Schools for interviews. The result findings from teacher questionnaires revealed that English teaching problems involving teachers, students, curricula & textbooks and other factors contributing to successful teaching were agreed as a high level of agreement. However, problems involving assessment was moderately agreed. In addition, the results findings from student questionnaires to investigate their attitude toward English learning revealed that the top problematic factors were teachers’ using translation method, lack of teaching material and having difficulty in listening skill. The findings from the teachers’ interviews revealed that facilities issues including inadequate resources and facilities are the main problem and the students were not motivated to study English and they lacked practice on their own. The solutions to overcome these challenges suggested in this study were reforming attitude of students and teachers and improving resources and facilities. On the other hand, applying various teaching methods and techniques, matching students’ proficiency level and learning situation, making use of available resources and facilities, providing motivational feedback, looking for appropriate methods or materials, and teachers’ self-reflection are the main solutions of the English teaching challenges. For further research, the main suggestion of this study is that more studies should be conducted to analyze English teaching problems not only High Schools in Taunggyi city but also High Schools around Myanmar using a larger number of teachers and students and using different research tools for collecting data.